Construction of an Adaptive Blended Curriculum (ABC) model in implementing local content curriculum - Zahid Zufar At Thaariq; Muhamad Fahmi Yulianto; Reno Nurdiyanto (Inovasi Kurikulum, 2023)
Indonesia is famous for its rich and diverse local wisdom. This diversity makes the wealth of human resources has the potential that can be developed in the realm of local content curriculum. It clearly aims to maintain Indonesia's cultural and natural diversity, and can be a source of local economic development and environmental sustainability. Through these considerations, this article reviews the construction of an adaptive blended curriculum (ABC) model that aims to manifest the potential of local content using a narrative approach. This implies that the author presents the results of the review based on existing literature. The review revealed the ABC Model as a curriculum construct oriented towards a combination of adaptive learning, adaptive curriculum and blended learning concepts adaptable to existing local potential. So, the submission of this model is considered important to optimize regional potential through the application of local content curriculum. Thus, this article can be used as a consideration of appropriate curriculum models that optimize the potential of local wisdom in Indonesia.AbstrakIndonesia terkenal dengan kearifan lokal yang sangat kaya dan beragam. Keberagaman ini menjadikan kekayaan sumber daya manusia memiliki potensi yang bisa dikembangkan dalam ranah kurikulum muatan lokal. Ini secara jelas bertujuan untuk mempertahankan keanekaragaman budaya dan alam Indonesia, serta dapat menjadi sumber pengembangan ekonomi lokal dan keberlanjutan lingkungan. Melalui pertimbangan tersebut, maka artikel ini meninjau konstruksi model adaptive blended curriculum (ABC) yang bertujuan untuk memanifestasikan potensi muatan lokal dengan menggunakan pendekatan naratif. Ini berarti penulis memaparkan hasil tinjauan berdasarkan literatur-literatur yang ada. Hasil tinjauan mengungkapkan Model ABC sebagai konstruk kurikulum yang berorientasi pada gabungan konsep adaptive learning, adaptive curriculum dan blended learning yang bisa diadaptasikan dengan potensi lokal yang ada. Maka, pengajuan model ini dirasa penting untuk mengoptimalkan potensi daerah melalui penerapan kurikulum muatan lokal. Dengan demikian, artikel ini bisa dijadikan sebagai bahan pertimbangan model kurikulum tepat guna (appropriate) yang mengoptimasi potensi kearifan lokal di Indonesia.Kata Kunci: Kurikulum muatan lokal; model ABC; model kurikulum